2018
DOI: 10.1016/j.addbeh.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Short message service (SMS) reminders improve treatment attendance in alcohol dependence, but are less effective for patients high in impulsivity

Abstract: SMS appointment reminders improve treatment attendance for alcohol-dependent outpatients. More impulsive patients benefited less from reminders, suggesting their non-attendance may be related more to motivational factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It may be that some of the characteristics of ADHD could make treatment adherence more challenging than in other patient groups ( 12 ). For instance, a study that examined the effect of SMS reminders on treatment adherence among patients with alcohol dependence found that those with higher levels of impulsivity benefitted less from SMS reminders ( 45 ). However, Biederman et al ( 31 ) found that SMS reminders improved adherence to pharmacological treatment among adults with ADHD, indicating that SMS reminders may be effective for this patient group as well.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that some of the characteristics of ADHD could make treatment adherence more challenging than in other patient groups ( 12 ). For instance, a study that examined the effect of SMS reminders on treatment adherence among patients with alcohol dependence found that those with higher levels of impulsivity benefitted less from SMS reminders ( 45 ). However, Biederman et al ( 31 ) found that SMS reminders improved adherence to pharmacological treatment among adults with ADHD, indicating that SMS reminders may be effective for this patient group as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a health service platform, caring messages are continuously delivered to patients via SMS [21], e.g., medication reminders [16,22] and to perform healthy behaviors [23]. As a result, the compliance of patients with self-care can be further improved [24,25], which is specific in the attendance rate of outpatient appointments [26][27][28]. In a web-based disease management system, it is feasible to use interactive SMS diaries to collect patient's disease data, i.e., patients send the messages of self-monitored physical conditions and receive disease management advice from doctors.…”
Section: Literature Review: Sms Application Areasmentioning
confidence: 99%
“…In order to conduct analysis and find insight, following the priori investigations of SMS as an intervention method in [15,16,18,23,26,[46][47][48][49][50][51][52][53][54][55], we chose gender and age as influencing factors to further explore the attitudes' differences towards COVID-19 publicinterest SMS in research questions. Cho et al adopted gender and age as the controlled factors and then indicated significant differences between females and males on attitudes towards SMS [46].…”
Section: Research Questionsmentioning
confidence: 99%
“…The GUI-based Short Messaging Service (SMS) network between handheld devices develops another useful application with the mobile device [10]. It is a cost-effective solution for monitoring common home appliances because mobile phones are already a staple in society's daily living.…”
Section: Mobile Phone Graphical User Interface (Gui) For Appliance Remote Control: An Sms-based Electronic Appliance Monitoring and Contrmentioning
confidence: 99%